Shareholder litigation risk and the information environment: Revisiting evidence from two natural experiments - Boone, Audra; Fich, Eliezer; Griffin, Thomas (Journal of Corporate Finance, 2023)
A court case that reduced securities class action litigation risk led to less frequent voluntary disclosure but did not significantly alter information asymmetry among market participants. Conversely, state laws that reduced derivative litigation risk led to more frequent voluntary disclosure but resulted in significantly higher information asymmetry. To reconcile these differences, we highlight that 10b-5 securities class actions address disclosure, while derivative suits can address broader corporate wrongdoing, leading to differential effects on firm operations. Our results suggest that the observed effect of derivative litigation risk on the information environment is primarily driven by concomitant changes in firm operations.